ANALISIS PERBANDINGAN DIAGNOSTIC REFERENCE LEVEL (DRL) MODALITAS CT SCAN SEBAGAI UPAYA OPTIMASI PROTEKSI DAN KESELAMATAN RADIASI DI BERBAGAI NEGARA - Duandini, Ega; Etika, Eva Anggun; Nurulita, Syaphira Faza; Hidayanto, Eko (BERKALA FISIKA, 2021)
Computed Tomography (CT) Scan had grown since its first discover at 1972. Now, CT Scan is the most capable radiodiagnostic modality for detecting human anatomy in a short time. However, CT Scan has the highest dose among another radiodiagnostic modalities. If radiation dose exposure exceeds the limit, it will cause any serious disease, such as cancer. Based on Mathews et al research in Australia, in 2016, there are 3150 from 680211 cancer patient ever exposured by CT Scan one year before. From the research, it is known that there is effect after exposured by CT Scan. Therefore, supervision is needed in an effort to ensure protective efficiency and safety of radiation against radiation workers, patients and communities, among them with the diagnostic reference level (DRL). The DRL is the value of a dose or rate of dosage or activity established by a data dose or rate of dosage or activity that X-ray medical examinations result from each type of examination. The value of the DRL is recommended on quartile 3 (75 percentiles) of a fragmented dose data obtained from the median value. This research focused on the CT scan modality for inspection. And obtained CTDIvol and DLP grades. In this research, obtainer DRL value for CT Chest 10.99 mGy CTDIvol and 411.71 mGy.cm DLP, and for CT Abdomen 17.84 mGy CTDIvol and 1298.58 mGy.cm DLP.